Perioperative Care of the Neonate - Budden, Lilian (Operating Room Nurses Association of Canada Journal, 1993)
The neonate is a unique individual with his\her own needs. This article deals with the adjustments the neonate has to make to extrauterine life; some of the differences between neonates and older children and adults, and the special needs of the neonate who needs surgery.